lNTERNALISASI NILAI LIFESTYLE DALAM MEWUJUDKAN MASYARAKAT MADANI (Studi Fenomenologi Gaya Hidup Guru MTsN Di Kota Malang Pasca Sertifikasi) - Zuhroh, Ni'matuz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Teacher professions in Indonesia were initially underestimated because they only received low salaries and were not standard when compared to other professions such as the lawyer's profession, the medical profession, and the accounting profession. Whereas in Japan, being a teacher is a dream for all young people because the Teacher's profession has been equated with other professions since 1886. But in the Era of President Susilo Bambang Yudhoyono's Government, through Law No. 14 of 2005 concerning Teachers and Lecturers, the fate of Master was raised as high as possible through Teacher Certification. The aspect of consumer needs in fulfilling their daily needs since the teacher received a certification allowance is a phenomenon that the condition of the teacher is better than the previous conditions. This research uses phenomenological qualitative methods. Based on the results of the study in general the certified teachers in Madrasah Tsanawiyah Negeri in Malang City have a fairly high spirit in carrying out the tasks which are realized, among others in the form of certification allowances functioned to improve self-quality by attending training, workshops, and seminars and buying equipment and supplies sufficient to support teaching.Keywords: professionals; lawyers; doctors; accountants; certifications